2016
DOI: 10.1080/10790268.2016.1141470
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic stretch enhances apoptosis in human lumbar ligamentum flavum cells via the induction of reactive oxygen species generation

Abstract: Objective: The lumbar ligamentum flavum (LF) is an important part of the spine to maintain the stability of the spine. In this study we aimed to examine whether mechanical force by cyclic stretch could induce apoptosis in human LF cells and investigate the underlying mechanism. Methods: LF cells were isolated from six young patients undergoing spinal surgery and then cultured in vitro. LF cells were subjected to cyclic stretch and the poptosis was detected by flow cytometry. The level of intracellular reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
(34 reference statements)
0
16
0
Order By: Relevance
“…CSA changes of 10-20% correspond to 70-80% changes in total lung capacity, according to morphometric analysis [19]. Additionally, 20% and 30% changes in CSA resulted in apoptosis in human and rat cells [20,21]. According to previous reports, 10% CSA and a uniaxial stretching direction were commonly applied in cyclic stretched lung cells [22][23][24][25][26][27][28].…”
Section: Cell Surface Area (Csa) Determinationmentioning
confidence: 93%
“…CSA changes of 10-20% correspond to 70-80% changes in total lung capacity, according to morphometric analysis [19]. Additionally, 20% and 30% changes in CSA resulted in apoptosis in human and rat cells [20,21]. According to previous reports, 10% CSA and a uniaxial stretching direction were commonly applied in cyclic stretched lung cells [22][23][24][25][26][27][28].…”
Section: Cell Surface Area (Csa) Determinationmentioning
confidence: 93%
“…It is known that the various effects of mechanical stretch on muscle cells result from the type of the stretch (i.e., duration, magnitude, and frequency of the stimuli) [Tan et al, 2009;Song et al, 2012;Chen et al, 2016] as well as the type of the cell [Sandri et al, 2001;Du et al, 2017]. Earlier studies have found that cell proliferation is tremendously influenced by the frequency of the mechanical stretch [Qiu et al, 2006;Hu et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…The various effects of mechanical stretch on skeletal muscle are considered to result from disparities in the duration, magnitude, and frequency of the stretch [Bardouille et al, 1996;Song et al, 2012;Chen et al, 2016]. Generally, a skeletal muscle cell is activated to proliferate if the mechanical load is appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in cell culture technology have assisted in vitro investigations of LFH [9,10]. No LF cell line is commercially available, and most studies employ primary fibroblast-like LF cells derived from patients.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have employed traditional two-dimensional (2D) culture platforms and animal models. In previous studies, LF cells were cultured in monolayers and subjected to different chemical or mechanical investigations, such as the induction of different growth factor [ 9 ] conditions or application of cyclic mechanical stimuli [ 10 ]. Other studies have also attempted to employ animal models to investigate LFH [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%